Academic staff's attitude toward the Bologna process and the new pedagogy in the University of Garmian - Omer Mahmood (Zanco Journal of Pure and Applied Sciences, 2021)
Throughout the last two decades, the world has witnessed an expansion of the process of Bologna from Europe towards countries from other continents such as Africa, South America, and Asia. Recently, the process has drawn Kurdistan regional government attention. Some of the Universities in Kurdistan have already implemented the process. On that base, the new vision of the University of Garmian has been to improve the quality of education to meet the international standards by implementing the Bologna process. In this study, the researchers aimed to investigate the potential of success of this process and the necessary preparations required by evaluating the attitudes of the academic staff of the University of Garmian towards the Bologna process. The research adopts a survey method (n=115) with academics at the university who were exposed to an intensive Bologna and pedagogy training course. The research findings suggest the possibility of implementing the process because of a number of helpful aids like, quantity of academic staff and the reasonable infrastructure of the University. However, regarding the challenges and barriers ahead of this process, the academics referred to the necessity of some technical and administrative improvement before implementing such an important process. These were: providing the classrooms with high-speed internet services, running continuous courses about the process, establishment of a directorate or a board to follow up the process and finally initiating better learning environment for the staff and students.